Impact of the eKutir ICT-enabled social enterprise and its distributed micro-entrepreneur strategy on fruit and vegetable consumption: A quasi-experimental study in rural and urban communities in Odisha, India. (January 2020) - Dubé, Laurette; McRae, Cameron; Wu, Yun-Hsuan; Ghosh, Samik; Allen, Summer; Ross, Daniel; Ray, Saibal; Joshi, Pramod K.; McDermott, John; Jha, Srivardhini; Moore, Spencer
Highlights: ICT-enabled ecosystems improve fruit and vegetable consumption for farmers in Odisha. Farm-level homegrown consumption mediates overall fruit and vegetable consumption. Retail interventions must go beyond improving access and focus on demand generation. Intersectoral policy-making approaches are needed to bridge value chain efforts. Abstract: This paper reports results of a quasi-experimental study designed to assess the impact of an information and communication technology (ICT) –enabled ecosystem, led by the social enterprise eKutir, on household fruit and vegetable consumption in Odisha, India. eKutir aims at providing self-sustaining solutions to poverty and undernutrition in developing countries by leveraging ICTs through ecosystem development anchored into a distributed micro-entrepreneurial strategy. eKutir's farming micro-entrepreneurs (FME) provide agricultural knowledge, inputs, and market linkages at household and community level, followed by progressive integration of other micro-entrepreneurs at different points along the value chain on both supply and demand sides. The present case examined core FMEs along with retail micro-entrepreneurs (RMEs) deployed in low-resource rural and urban communities. Structural equation modeling was used to compare rural outcomes and the role of homegrown consumption as a mediator. Multivariable linear regression and ANOVA were used to test group differences in the urban sample. Positive β coefficients represent an increase in fruit and vegetable consumption in communities exposed to the eKutir ecosystem in contrast to the comparison group. Farmers in rural communities exposed to the eKutir ecosystem consumed more overall fruit and vegetables (β = 0.30, p < 0.001) and fruits alone (β = 0.53, p < 0.05) than those farmers in comparison villages unexposed to the eKutir ecosystem. This effect was concentrated in households exposed to both FMEs + RMEs (β = 0.60, p < 0.0001) and was mediated by homegrown consumption. A non-significant directional effect was observed in comparing fruit and vegetable consumption in rural households exposed to RMEs only over comparison communities. Urban consumers, exposed to the eKutir ecosystem through access to RMEs operating in their neighborhood community, did not increase their fruit or vegetable consumption compared to non-intervention communities. The results reveal the potential of reaching nutritional impacts through homegrown consumption and with farm-level support outside of governmental/philanthropic interventions through an ICT-enabled social enterprise. They also underscore, however, the challenges of both changing eating behaviour and intervening along the agri-food value chain. Implication for more effective digital ecosystem design and intersectoral policies are discussed.